Respostas

2013-10-23T16:32:58-02:00
A=1 b=-2 c=-48  

/\=b²-4.a.c
/\=(-2)²-4.(1).(-48)
/\=4+192
/\=196
x=-b +- raiz de delta
              2.a 
x=-(-2) +- raiz de 196
                2.1
x=2+- 14 
        2 
x¹= 2+14 = 16 = 8 
         2        2 
x²=2-14 = -12 =- 6 
      2        2 

obs** no x² é -12
então o resultado é -6
vou editar
2013-10-23T16:38:18-02:00
 x^{2} - 2x - 48 
x= -b \sqrt \alpha /2.a

 \alpha = ( b^{2} - 4.a.c
 \alpha = ( -2^{2} ) - 4.1.(-48)
 \alpha = 4 + 192
 \alpha = 196

x= -(-2)\sqrt{196} /2
x= 2 +- 14/2
 x_{1} = 2+14/2= 8
 x_{2} = 2- 14/2= -6

Espero ter ajudado